Development of self-polishing antifouling paint with cerium oxide nanoparticle additives - Kambuna, Bening; Dwiyanti, Yanyan; Nikitasari, Arini; Prasetyo, Muhammad Imam; Rahman, Aditya (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2025)
The research on self-polishing antifouling paint with cerium oxide nanoparticle additives represents a significant advancement in ship protection technology. This study aims to develop a more effective and environmentally friendly solution to prevent the growth of fouling organisms, a persistent issue in the maritime industry. Cerium oxide nanoparticles are employed to reduce the release rate of copper, the active component in many antifouling paints. The study investigates (1) the effect of cerium oxide concentration on the copper (Cu) release rate and hydrophobicity of the antifouling paint, (2) the impact of salinity on these properties, and (3) differences in the coating mechanism between paints with and without cerium oxide additives. Cerium oxide nanoparticles (50 nm) were incorporated into the paint at concentrations of 0.1%, 0.2%, 0.3%, 0.4%, and 0.5%. The coated samples were immersed in synthetic seawater and Tanjung Pasir seawater for 45 days. Results show that different CeO₂ concentrations influence the release rates of Cu and zinc (Zn). A 0.2% concentration of CeO₂ yielded the highest Cu release rate at 1.4778 µg/cm², while the highest Zn release rate (0.234 µg/cm²) was observed at 0.5% CeO₂. Additionally, CeO₂ additives altered the surface characteristics of the antifouling paint, increasing its hydrophilicity as indicated by contact angle values dropping below 90°.